PDFs in the indexing process. (June 2018) - Greulich, Walter
Abstract : Walter Greulich explores the various ways in which PDFs can be used in the indexing process, offering advice on techniques and suitable PDF programs, and suggests a method which brings indexing with PDFs very close to offering the functionality of embedded indexing. He addresses the needs of both the professional indexer working alone and the team situation where a combination of professional and non-professional indexers work together on a project.